An elderly patient with Bickerstaff brainstem encephalitis: a case report - Rashedul Islam, Md; Rahman, Tanbin; Sakhawat Hossen Khan, Mohammad; Azharul Islam, Md (BIRDEM Medical Journal, 2024)
Bickerstaff brainstem encephalitis is a rare autoimmune inflammatory disorder characterized by the triad of ophthalmoplegia, ataxia and decreased consciousness. It is considered as a variant of Miller Fisher syndrome and Guillain-Barré syndrome but differentiated by the presence of clinical features of central nervous system involvement. Here, we present a case of Bickerstaff’s brainstem encephalitis with classical clinical features, suggestive radiological findings and positive anti-GQ1b antibody. BIRDEM Med J 2024; 14(1): 53-56